# Solve for y 1/4*(2y-3)=1/2y-3/4

14⋅(2y-3)=12y-34
Simplify 14⋅(2y-3).
Apply the distributive property.
14(2y)+14⋅-3=12y-34
Cancel the common factor of 2.
Factor 2 out of 4.
12(2)(2y)+14⋅-3=12y-34
Factor 2 out of 2y.
12(2)(2(y))+14⋅-3=12y-34
Cancel the common factor.
12⋅2(2y)+14⋅-3=12y-34
Rewrite the expression.
12y+14⋅-3=12y-34
12y+14⋅-3=12y-34
Combine 12 and y.
y2+14⋅-3=12y-34
Combine 14 and -3.
y2+-34=12y-34
Move the negative in front of the fraction.
y2-34=12y-34
y2-34=12y-34
Combine 12 and y.
y2-34=y2-34
Move all terms containing y to the left side of the equation.
Subtract y2 from both sides of the equation.
y2-34-y2=-34
Combine the opposite terms in y2-34-y2.
Subtract y2 from y2.
0-34=-34
Subtract 34 from 0.
-34=-34
-34=-34
-34=-34
Since -34=-34, the equation will always be true for any value of y.
All real numbers
The result can be shown in multiple forms.
All real numbers
Interval Notation:
(-∞,∞)
Solve for y 1/4*(2y-3)=1/2y-3/4

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top